1989
DOI: 10.1029/ja094ia04p03579
|View full text |Cite
|
Sign up to set email alerts
|

Energy spectra of the major ion species in the ring current during geomagnetic storms

Abstract: Using the University of Maryland/Max‐Planck‐Institut für Aeronomie charge‐energy‐mass (CHEM) spectrometer on the AMPTE Charge Composition Explorer (CCE) spacecraft, we have examined the nearly equatorial storm time energy spectra of four major magnetospheric ions, H+, O+, He+, and He++, over the energy range 1–300 keV/e in the L range 3–6. The data were obtained during the main and early recovery phases of all geomagnetic storms with minimum Dst less than −50 nT in the time period September 1984 to November 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
188
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(200 citation statements)
references
References 49 publications
12
188
0
Order By: Relevance
“…To investigate this further we simulated ring current dynamics during this event using an eastward offset of 2 hours in the convection electric field. Previous studies [e.g., Gussenhoven et al, 1981;Matsui et al, 2004] have indicated that the symmetry axis of the plasma convection pattern may be rotated by a few hours from the dawn-dusk direction during disturbed periods, and better agreement between measured and observed ion fluxes can be obtained if an offset is applied [e.g., Kistler et al, 1989;Jordanova et al, 1999]. A rotation of the axis of symmetry and further distortion of the electric field may be due to disruptions of electric field shielding and fieldaligned currents, as well as changes in the near-terminator conductivity gradient or in the magnetic configuration [Wolf et al, 2005, and references therein].…”
Section: A08209mentioning
confidence: 99%
“…To investigate this further we simulated ring current dynamics during this event using an eastward offset of 2 hours in the convection electric field. Previous studies [e.g., Gussenhoven et al, 1981;Matsui et al, 2004] have indicated that the symmetry axis of the plasma convection pattern may be rotated by a few hours from the dawn-dusk direction during disturbed periods, and better agreement between measured and observed ion fluxes can be obtained if an offset is applied [e.g., Kistler et al, 1989;Jordanova et al, 1999]. A rotation of the axis of symmetry and further distortion of the electric field may be due to disruptions of electric field shielding and fieldaligned currents, as well as changes in the near-terminator conductivity gradient or in the magnetic configuration [Wolf et al, 2005, and references therein].…”
Section: A08209mentioning
confidence: 99%
“…[17] O + ions can be a significant contribution to the trapped ion population in the ring current during geomagnetic storms [Kistler et al, 1989]. Mitchell et al [2003] showed how O + could be distinguished from H + in ENA images.…”
Section: Themismentioning
confidence: 99%
“…The ion spectra observed on the dayside typically contain one or more minima which correspond to the drift paths on which the greatest losses occur, either because they have the longest drift time, or because they drift the closest to the Earth, where losses are greater. Many studies (e.g., Kistler et al, 1989;Fok et al, 1996;Jordanova et al, 1999) have shown qualitative agreement between observed and predicted spectra based on these principles. However, there has been di culty in getting quantitative agreement.…”
Section: Introductionmentioning
confidence: 99%